Que tiro foi esse?: um estudo dialógico das metáforas cotidianas - Silva, Letícia Karine Alves da (2024)
The use of social networks as a space for human interaction has intensified in recent years, influencing collective perceptions and public discourses. Such interactions reflect social, cultural and political issues, making digital platforms relevant objects of study for linguistic analysis. Thus, having as motivation the production of controversial speeches involving metaphors of violence, such as "process or bullet" and "what shot was that", coming from two distinct discursive genres, this research chose as its main objective to understand the meaning effects of metaphors in digital interactions and the dynamics of responsiveness between speakers and interlocutors. The research set out to explore how metaphors can be used in contexts of symbolic violence and the challenges of interpreting these statements as figures of speech or real threats. To answer this objective, four chapters were created. The first sought a definition of metaphor from a philosophical perspective, based on Ricouer (2000) and from a linguistic-cognitivist perspective, based on Lakoff and Johnson (1980). The second chapter sought, with theoretical support from Bakhtin (2010; 2016) and Volochínov (2018), to outline main concepts arising from the perspective of language, with a view to understanding the effects of meaning produced by comments from social media users on the two statements motivators. The third chapter describes the methodological procedures and the fourth chapter presents the analyzes of ten comments, exploring how social media users interpret these discourses, seeking to understand the effects of meaning produced, based on the identification of the use of metaphors or discourse that was made incitements to violence. The research carried out revealed that the meanings attributed to statements on social networks are constructed collectively, being strongly influenced by social and historical contexts, reflecting the experiences and intentions of those who produce them and that the justification for using metaphors is not always theoretically supported.